EFFECTIVENESS OF IRON SUPPLEMENTATION PROGRAMS IN PREVENTING ANEMIA AMONG PREGNANT WOMEN: SYSTEMATIC LITERATURE REVIEW - Nasywa Dwi Ayu Suhendi; Ummi Hanidah; Nafis Ikhwana; Brooklyn Razan; Deskia Amanda (Journal of Research in Pharmacy and Pharmaceutical Sciences, 2025)
Anemia in pregnancy remains a major public health issue in Indonesia, contributing to maternal and fetal complications. This study aims to assess the effectiveness of iron supplementation in preventing anemia among pregnant women through a systematic literature review using PRISMA guidelines. A total of 12 eligible articles published from 2016 to 2025 were analyzed, focusing on the Indonesian population. The findings consistently demonstrate that iron and folic acid supplementation significantly increases hemoglobin levels and reduces anemia prevalence in pregnant women. However, adherence to supplementation is a persistent challenge. Only 53.4% of pregnant women consumed iron tablets for at least 90 days, with adherence influenced by maternal education, socioeconomic status, access to healthcare, and family support. While most studies confirmed the biological effectiveness of iron supplementation, limitations such as small sample sizes, limited geographic coverage, lack of control groups, and short-term observation periods were noted. To optimize outcomes, a multidimensional approach involving health education, improved healthcare access, and community support is essential. Strengthening adherence and monitoring mechanisms can enhance the long-term impact of iron supplementation in reducing maternal anemia in Indonesia.